The Influence of Asymmetrical Formation from Makassar Basin to the Geochemical Characteristics of Mallawa Formation - Sutadiwiria, Yarra; Ronoatmojo, Imam Setiaji; Fathaddin, Muhammad Taufiq; Rendy; Riyandhani, Cahyaningratri Prima; Yusuf, Ariq Haykal; Aufariq Asaria Cifa; Mordekhai; Yeftamikha; Amalia; K.Gunawan, Brahmantyo (UIR PRESS, 2025)
A functional hydrocarbon system relies on three key elements: source rock, reservoir rock, and seal rock. These components are essential in assessing the hydrocarbon potential of a region. In South Sulawesi, the Makassar Basin shows promise for petroleum development, particularly with the Mallawa Formation an Early to Late Eocene unit serving as a potential source rock. Source rocks play a critical role in generating and storing hydrocarbons. Indonesia’s frequent oil and gas exploration activities are driven by the presence of numerous prospective hydrocarbon-bearing areas. It's crucial to recognize that source rocks typically form within sedimentary basins. The Makassar Basin, a land-based Tertiary sedimentary basin situated along western and southern Sulawesi, originated from tectonic activity, specifically the widening of the Makassar Strait, which began no later than the Early Paleocene. This tectonic evolution significantly affected the thermal maturation of the basin’s source rocks. This study applies geochemical analysis of cutting samples to evaluate the maturity of these rocks. The findings contribute valuable understanding to hydrocarbon exploration in South Sulawesi, a region characterized by a complex tectonic framework. The results of laboratory analyses show that sustainable hydrocarbon exploration may be possible in South Sulawesi, especially in Balangbaru Formation, which is believed to be a potential source rock, in addition to the Mallawa Formation.